Meta-analysis of minimally invasive transforaminal lumbar interbody fusion versus oblique lumbar interbody fusion for treating lumbar degenerative diseases - Dun Liu; Xinyu Huang; Chongyang Zhang; Qin Wang; Hua Jiang (Journal of Orthopaedic Surgery and Research)
Abstract Objective This study aims to perform a meta-analysis that integrates multiple literature sources to evaluate the clinical efficacy of oblique lumbar interbody fusion (OLIF) versus minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) for treating lumbar degenerative diseases (LDD). Methods A systematic search was conducted across various databases, including CNKI, VIP, WANFANG DATA, SinoMed, PubMed, Cochrane Library, Embase, and Web of Science, for clinical comparative studies on OLIF and MIS-TLIF for treating LDD, covering the time frame from the inception of the databases to September 2024. Following PRISMA guidelines, studies were screened, assessed, and data were extracted rigorously. Indicators extracted included operative time, intraoperative blood loss, hospital stay, visual analog scale (VAS) scores, Oswestry Disability Index (ODI), disc height (DH), segmental lordotic angle (SLA), lumbar lordosis angle (LLA), postoperative JOA scores, patient satisfaction, complication rates, and fusion rates. Meta-analysis was performed using Review Manager 5.4 software. Results A total of 24 studies were included, comprising 11 randomized controlled trials and 13 retrospective cohort studies. The total population consisted of 1785 patients, with 898 in the OLIF group and 887 in the MIS-TLIF group. The meta-analysis indicated that, compared to the MIS-TLIF group, the OLIF group exhibited significantly lower intraoperative blood loss, shorter hospital stays, improved postoperative DH, shorter operative time, reduced postoperative VAS scores, lower postoperative ODI scores, and improved postoperative SLA and LLA. No significant differences were observed between the groups in postoperative JOA scores, fusion rates, complication rates, or patient satisfaction. The OLIF group exhibited advantages such as lower blood loss, shorter hospital stays, higher postoperative fusion rates, and improved recovery of disc and foraminal heights. Conclusion Compared to MIS-TLIF, OLIF is associated with a shorter operative time and less intraoperative blood loss, potentially leading to better relief of leg pain, restoration of DH, and prevention of subsidence. These findings offer valuable insights for clinical practice.